Barbara Frishmuth’s Novel “Time of Ripening”: Specificity of a Philological Novel - L. V. Trofimova (Научный диалог, 2019)
The article is devoted to one of the newest genres of literary criticism - philological novel. Material for the study was the work of the contemporary Austrian writer Barbara Frishmuth - “Time of Ripening.” The novelty of the research is seen in the fact that Frishmuth’s works are little studied in the domestic literature, and this novel was not analyzed by Russian scientists. The proposed research coordinate system considers literary approach to addressing problems in the modern literature, including B. Frishmuth’s works. The author dwells on the characterization of the novel’s main character - a philologist, creative personality, whose creative abilities are manifested in the spontaneity of the world view, inner freedom, desire to comprehend the irrational mystery of creativity. It is shown that this novel has a complex composition associated with the interweaving of different chronological plans; driving force of the story is a mystery. The question of the set of realities and fiction in the depicted world of the work is raised. Special attention is paid to the fact that not only the narrator but all the characters in the novel are involved in the literary activities: specialists in medieval cryptography plunge into the mysterious text, they gradually begin to understand that they faced with one of the fantastic mysteries of the past - amazing conversation between a great Eastern poet with a German Prelate of a small monastery, who were divided by a century.